1999
DOI: 10.1046/j.1365-2672.1999.00600.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection and quantification of yeast species during spontaneous wine fermentation by PCR-RFLP analysis of the rDNA ITS region

Abstract: L. GRANCHI, M. BOSCO, A. MESSINI and M. VINCENZINI.1999.PCR–RFLP analysis of the rDNA–ITS (internal transcribed spacer) region was applied to 174 yeast strains belonging to 30 species of oenological significance and including 27 type strains in order to define a rapid identification protocol for yeast colonies. DraI‐or HaeIII‐PCR–RFLP patterns were species‐specific with the exception of teleomorphic and anamorphic forms. An improved protocol taking about 30 h was used for the detection and quantification of ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
100
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(113 citation statements)
references
References 23 publications
10
100
1
2
Order By: Relevance
“…We have conducted our analysis by considering 59 Candida isolates of the non-Saccharomyces IRVV collection. These were initially identified as representative of Candida stellata (Romancino et al, 2008), based on microbiological (Cavazza & Poznanski, 1998) and molecular analyses (Esteve-Zarzoso et al, 1999;Granchi et al, 1999). As new studies showed the prevalence of the C. zemplinina species in wine musts (Csoma & Sipiczki, 2008), we reanalysed our isolates and were able to establish that all of them belonged to the C. zemplinina species.…”
Section: Characterisation Of the Candida Zemplinina (Cz) Isolatesmentioning
confidence: 99%
“…We have conducted our analysis by considering 59 Candida isolates of the non-Saccharomyces IRVV collection. These were initially identified as representative of Candida stellata (Romancino et al, 2008), based on microbiological (Cavazza & Poznanski, 1998) and molecular analyses (Esteve-Zarzoso et al, 1999;Granchi et al, 1999). As new studies showed the prevalence of the C. zemplinina species in wine musts (Csoma & Sipiczki, 2008), we reanalysed our isolates and were able to establish that all of them belonged to the C. zemplinina species.…”
Section: Characterisation Of the Candida Zemplinina (Cz) Isolatesmentioning
confidence: 99%
“…To achieve greater polymorphism, the amplified genes were treated with the restriction enzymes CfoI, HinfI, and HaeIII for the identification of yeasts at the species level (ESTEVE ZARZOSO et al, 1999;GRANCHI et al, 1999). The PCR amplified 5.8S ITS rRNA region was sequenced using the ABI Prism 3100 genetic analyzer.…”
Section: Introductionmentioning
confidence: 99%
“…PCR products varying in length from 390 to 880 bp were digested with HinfI, HaeIII and DdeI enzymes, and the molecular mass of the restriction products obtained was compared with those described previously in the literature [10][11][12][13]. In general, we observed 18 different profiles of the ITS-5.8S rDNA region.…”
Section: Resultsmentioning
confidence: 76%
“…The approximate lengths were determined by the use of molecular weight ladder (100 bp, Roche). PCR and RFLP fragment lengths were used for identification of yeasts by comparison of the restriction bands with those available in literature [10][11][12][13]. Several groups appeared on the basis of their RFLP of the ITS region.…”
Section: Methodsmentioning
confidence: 99%